2016
DOI: 10.1371/journal.pone.0160741
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei Biofilm Promotes Adhesion, Internalization and Stimulates Proinflammatory Cytokines in Human Epithelial A549 Cells

Abstract: Burkholderia pseudomallei is a Gram-negative bacterium that causes melioidosis. Inhalational exposure leading to pulmonary melioidosis is the most common clinical manifestation with significant mortality. However, the role of B. pseudomallei biofilm phenotype during bacterial-host interaction remains unclear. We hypothesize that biofilm phenotype may play a role in such interactions. In this study, B. pseudomallei H777 (biofilm wild type), B. pseudomallei M10 (biofilm mutant) and B. pseudomallei C17 (biofilm-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 49 publications
2
55
0
Order By: Relevance
“…It is possible that B. pseudomallei adaptation might employ biofilm formation for survival [ 61 ]. This concurs with a previous study that found that the biofilm of B. pseudomallei increased bacterial adherence to host cells [ 75 ]. The T6SS genes, which encode proteins that facilitate cell-to-cell spreading, are reportedly induced by iron deprivation [ 76 ].…”
Section: Molecular Mechanisms For B Pseudomallei supporting
confidence: 93%
“…It is possible that B. pseudomallei adaptation might employ biofilm formation for survival [ 61 ]. This concurs with a previous study that found that the biofilm of B. pseudomallei increased bacterial adherence to host cells [ 75 ]. The T6SS genes, which encode proteins that facilitate cell-to-cell spreading, are reportedly induced by iron deprivation [ 76 ].…”
Section: Molecular Mechanisms For B Pseudomallei supporting
confidence: 93%
“…Potential bacterial toxicity may be enhanced when cells are present in biofilms, which are heterogeneously sessile bacterial communities that adhere to each other and to solid surfaces (Wang et al, 2012 ). Kunyanee et al ( 2016 ) reported the important role of Burkholderia pseudomallei biofilms in bacterial pathogenesis in human epithelial cells with respect to initial attachment and invasion. In the Δ bcsR mutant of C. sakazakii , the decrease of biofilm formation suggests that this gene may affect adhesion/invasion by regulating biofilm synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Virulence factors like flagellin, Type III Secretion Systems (T3SS) [ 7 ], adhesins [ 5 ], pili [ 5 ], and biofilm [ 8 ] have all been described for B. pseudomallei and B. mallei. Actin-based motility [ 7 ] and flagellae permit rapid transit through cells.…”
Section: Discussionmentioning
confidence: 99%